Participación de los padres de familia en el proceso enseñanza aprendizaje de los niños de inicial II de la Escuela de Educación Básica 21 de Abril, cantón Riobamba, período 2020-2021 - Fiallos Lara, Mabel Estefania (2021)
The present research: "Participation of parents in the teaching learning process of children of initial II of the School “Escuela de Educación Básica 21 de Abril”, Riobamba canton, academic period 2020-2021". Its main objective was: to determine how the participation of parents influences the teaching learning process of children of initial II of the School “Escuela de Educación Básica 21 de Abril”. The reference framework of the research is the participation of parents in the teaching-learning process, it also explains the importance of parental participation, the consequences generated by the lack of participation and in which activities parents actively participate in the school life of their children. The subjects investigated were parents, a teacher, and 28 boys and girls. The type of research was basic because it is a social research because the participation of parents has been and is one of the main actors in the teaching and learning of their children. For data collection, instruments were used such as: workshop for parents, 1 observation sheet for 28 children, between 12 boys and 16 girls, and a survey for 1 teacher. Among the main results, it was found that the majority of parents do not participate in the teaching learning process of children from initial II. It is concluded that the parents of the school “Escuela de Educación Básica 21 de Abril”, do not participate in the teaching learning process of the children, that is why it is recommended to take into account that the more participatory they are, the better the results will be in the school performance of their children.